Revision of the Afrotropical species of Pareumenes de Saussure (Hymenoptera, Vespidae, Eumeninae) - Selis, Marco (Zootaxa, 2025)
A taxonomic revision of the Afrotropical species of the genus Pareumenes de Saussure, 1855 is presented. Three subgenera are recognized, namely Pareumenes s. str., Nortonia de Saussure, 1869 (= Afrorhynchium Gusenleitner, 2020, syn. nov.) and Brachyparmenes Giordani Soika, 1987 (= Interzumia Gusenleitner, 2002, syn. nov.). One new species, Pareumenes (Brachyparmenes) mirificus Selis, sp. nov., is described from Central African Republic. All the subspecies of Pareumenes (P.) sansibaricus (Schulz, 1905) are raised to species-level: P. (P.) arabicus Giordani Soika, 1981, stat. nov., P. (P.) flavopetiolatus Giordani Soika, 1944, stat. nov., P. (P.) laetefasciatus Giordani Soika, 1944, stat. nov., P. (P.) laterorufofasciatus Giordani Soika, 1944, stat. nov. and P. (P.) occidentalis Giordani Soika, 1944, stat. nov. New synonymies are proposed for Pareumenes (N.) laevis (von Schulthess, 1903) (= Afrorhynchium dathei Gusenleitner, 2020, syn. nov.) and Pareumenes (B.) rufoniger (Gusenleitner, 2002), comb. nov. (= Pareumenes mediator Gusenleitner, 2012, syn. nov.). A key to the Afrotropical species of Pareumenes is provided.